Nýrnafrumukrabbamein á Íslandi 1971-1990 : stigun og lífshorfur - klínisk rannsókn á 408 tilfellum - Tómas Guðbjartsson; Guðmundur V. Einarsson; Jónas Magnússon (Læknafélag Íslands, Læknafélag Reykjavíkur, 2009)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Incidence and mortality of renal cell carcinoma (RCC) is very high in Iceland. Studies have shown increased incidence of incidentally diagnosed RCCs. The significans of incidental diagnosis relating to survival of RCC patients is not known. A retrospective population-based study was carried out on all patients diagnosed with RCC between 1971 and 1990 in Iceland. The aim of the study was to evaluate survival of RCC patients in Iceland with emphasis on incidental diagnosis. By incidental diagnosis we mean tumours that were detected due to imaging techniques or an operation for other than RCC symptoms or signs. Of 236 males and 172 females diagnosed, 308 patients underwent radical nephrectomy with operative mortality of 2.6%. The tumours were classified and staged by Robson's method. Crude probability of survival was evaluated for every stage and multivariate analysis used to find prognostic factors. 224 patients presented with symptoms, the most common of which were abdominal pain, hematuria and weight loss. Between 1971 and 1980 15% of the patients were diagnosed incidentally and 20% between 1981 and 1990 (p>0.1), most often because of intravenous urography. Only 5 tumours were detected by ultrasound and 4 by CT-scans. Five year survival was 76% for stage I and 11% for stage IV. Advanced age, low haemoglobin and high ESR at diagnosis are significant independent risk factors of mortality in multivariate analysis. The year of diagnosis is not a significant prognostic factor after correction for stage. Survival of RCC patients in Iceland is comparable to that in neighbouring countries. Patients diagnosed incidentally have better survival because of a lower stage. The use of ultrasound and CT-scans has not significantly increased incidentally diagnosed tumours. Survival has remained the same for the last two decades. Nýgengi nýrnafrumukrabbameins er mjög hátt á Íslandi. Ekki er þekkt á hvaða stigi sjúklingarnir ...